theoretical bases of perspective chemical sources of current (CSC) and ultra-high-volume capacitor structures (UCS) for electric energy accumulators - Vladimir Vladimirovich, Sleptsov; Dmitry Yuryevich, Kukushkin; Anna Olegovna, Diteleva (International Journal of Engineering and Technology, 2018)
The paper analyzes thin-film technologies for advanced CSC and UCS. It is shown that the amount of accumulated energy is determined by the work of moving the charges in a given direction. This dependence determines the energy intensity of the CSC and UCS shows that the process of accumulation of electric energy in them is the same, and is determined mainly by polarization effects in the system. Because the mechanism of accumulation of electric energy in the CSC and UCS from a physical point of view is the same, there is a possibility to combine design solutions and to create a unified electrode material for a CSC and UCS in thin-film technology. In this case, it is possible to increase the specific energy capacity of the energy storage device while increasing its specific power in a single design solution. The traditional design of CSC and electrolytic UCS focused on the formation of electrode materials for thick-film technology. From this point of view, thin-film technologies, which have been actively developed recently, are promising. The prospect of developing thin-film technologies is associated with the use of nanomaterials and nanostructures, which can form more energy-intensive materials and significantly change the processes of converting the energy of the double electric layer and chemical interaction into electrical energy. The task of the article is to study thin-film technologies theoretically and experimentally in order to determine their development prospects for high-energy current sources, determine the ranges of their use and the possibility of industrial implementation. However, recently there has been a tendency to reduce the dynamics of growth in energy intensity of CSC generated by this technology.Â Â